Effects of a food-based intervention on markers of micronutrient status among Indian women of low socio-economic status. Issue 5 (13th February 2015) - Kehoe, Sarah H.; Chopra, Harsha; Sahariah, Sirazul A.; Bhat, Dattatray; Munshi, Renuka P.; Panchal, Falguni; Young, Stephen; Brown, Nick; Tarwande, Dnyaneshwar; Gandhi, Meera; Margetts, Barrie M.; Potdar, Ramesh D.; et al.
Abstract : Intakes of micronutrient-rich foods are low among Indian women of reproductive age. We investigated whether consumption of a food-based micronutrient-rich snack increased markers of blood micronutrient concentrations when compared with a control snack. Non-pregnant women ( n 222) aged 14–35 years living in a Mumbai slum were randomised to receive a treatment snack (containing green leafy vegetables, dried fruit and whole milk powder), or a control snack containing foods of low micronutrient content such as wheat flour, potato and tapioca. The snacks were consumed under observation 6 d per week for 12 weeks, compliance was recorded, and blood was collected at 0 and 12 weeks. Food-frequency data were collected at both time points. Compliance (defined as the proportion of women who consumed ≥ 3 snacks/week) was >85 % in both groups. We assessed the effects of group allocation on 12-week nutrient concentrations using ANCOVA models with respective 0-week concentrations, BMI, compliance, standard of living, fruit and green leafy vegetable consumption and use of synthetic nutrients as covariates. The treatment snack significantly increased β-carotene concentrations (treatment effect: 47·1 nmol/l, 95 % CI 6·5, 87·7). There was no effect of group allocation on concentrations of ferritin, retinol, ascorbate, folate or vitamin B12 . The present study shows that locally sourced foods can be made into acceptable snacks that may increase serum β-carotene concentrations among women of reproductive age. However, no increase in circulating concentrations of the other nutrients measured was observed.